Pyelonephritis in Japan caused by Salmonella enterica subspecies arizonae. Issue 12 (December 2017) - Nishioka, Hiroaki; Doi, Asako; Takegawa, Hiroshi
Abstract: Salmonella enterica subsp. arizonae is a bacteria commonly found in the gut of reptiles. In humans, infections caused by this organism are rare. Most cases originate from southwestern United States, where rattlesnake products are often used in traditional medicine. In Asia, only a few cases have been described. This case report documents a case involving a 64-year-old woman with pyelonephritis caused by S. arizonae in Japan. She had no history of contact with reptiles or foreign travel. The likely route of transmission is unclear. She was treated with cephalosporins for 14 days and the pyelonephritis appeared to be resolved; however recurrence occurred twice –after two weeks and then after one month. Prolonged antibiotic therapy with amoxicillin resolved the infection. This case demonstrates that pyelonephritis associated with S. arizonae can be found outside of the typical geographic region and may not be associated with typical animal hosts.